Tardy Aschner-Dagnini Reflex following Topical Pterygium Surgery: A Rare Case Report - Vikas Sharma; Ritesh Waghray; Anuradha Singh; Akanksha Sahu; Sandepan Bandopadhyay (Journal of Clinical and Diagnostic Research, 2023)
The Aschner-Dagnini reflex, also known as the Oculocardiac Reflex (OCR) or Trigeminovagal Reflex (TVR), is characterised by a reduction in heart rate due to direct pressure on the globe or traction on the Extraocular Muscles (EOM). It was first described in 1908 and is observed during strabismus surgery. However, it has also been reported following other ophthalmic procedures such as pterygium surgery or gonioscopy, as well as after facial trauma or regional anaesthesia. Sinus bradycardia is the most common presentation, accompanied by nausea and dizziness in conscious patients. In severe cases, it may also result in reduced blood pressure and life-threatening emergencies, including cardiac arrhythmias and arrest. Hereby, the authors present a rare case report of a 34-year-old male with delayed onset OCR following pterygium surgery under topical anaesthesia. The case was managed conservatively, as described in the case report, and the patient had a good recovery. To the best of authors’ knowledge, the present is the first reported case of OCR in the early postoperative period, following pterygium surgery.